WAYS TO ENSURE ECONOMIC SECURITY OF INDUSTRIAL ENTERPRISES IN THE TERRITORIES - Muminov Mirjalol Uktam ugli (Galaxy International Interdisciplinary Research Journal, 2022)
This article describes the ways to ensure the economic security of industrial enterprises in the regions. It is based on the importance of ensuring the economic security of industrial enterprises at the current stage of development. The issue of ensuring the economic security of enterprises is also covered by the scientific and theoretical views of foreign and domestic scientists. In addition, conclusions and recommendations on economic security of enterprises in our country are given.